2009
DOI: 10.1002/jmor.10777
|View full text |Cite
|
Sign up to set email alerts
|

Gill morphometrics in relation to gas transfer and ram ventilation in high‐energy demand teleosts: Scombrids and billfishes

Abstract: This comparative study of the gill morphometrics in scombrids (tunas, bonitos, and mackerels) and billfishes (marlins, swordfish) examines features of gill design related to high rates of gas transfer and the high-pressure branchial flow associated with fast, continuous swimming. Tunas have the largest relative gill surface areas of any fish group, and although the gill areas of non-tuna scombrids and billfishes are smaller than those of tunas, they are also disproportionally larger than those of most other te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 45 publications
3
88
0
Order By: Relevance
“…Direct oxygen tolerance measurements for adult billfishes are not available, although one juvenile sailfish (Istiophorus platypterus) study indicated high oxygen consumption and typical metabolic rates associated with tropical tunas 19 . These high-oxygen-demand species also share obligate ram ventilation respiration, large gill surface and intolerance to low ambient dissolved oxygen 15,17,20,21 . Here, we consider the plausible hypothesis that these species have oxygen limitations that impact vertical habitat use.…”
Section: Figure 1 | Blue Marlin M Nigricans With An Electronic Tag Umentioning
confidence: 99%
“…Direct oxygen tolerance measurements for adult billfishes are not available, although one juvenile sailfish (Istiophorus platypterus) study indicated high oxygen consumption and typical metabolic rates associated with tropical tunas 19 . These high-oxygen-demand species also share obligate ram ventilation respiration, large gill surface and intolerance to low ambient dissolved oxygen 15,17,20,21 . Here, we consider the plausible hypothesis that these species have oxygen limitations that impact vertical habitat use.…”
Section: Figure 1 | Blue Marlin M Nigricans With An Electronic Tag Umentioning
confidence: 99%
“…The genera Paratrygon and Plesiotrygon may be included in this group. Several authors agree that gill area is linked to the activity of the fish (Gray, 1954;Wegner et al, 2010). For example, the gill filament number is higher in the faster swimming Atlantic sharpnose Rhizoprionodon terraenovae (Richardson, 1836) than in more benthic smooth dogfish shark Mustelus canis (Mitchill, 1815) (Schwartz et al, 1993).…”
Section: Interspecific Variations Among Potamotrygonid Embryosmentioning
confidence: 99%
“…The gill dimensions can also be influenced by the level of an animal's activity. Both teleosts and elasmobranchs with high metabolic requirements have gill specialisations facilitating gas transfer De Jager & Dekkers, 1975;Wegner et al, 2010). Like teleosts, active pelagic elasmobranchs have a large gill area, densely packed lamellae, and a low water-blood barrier (Hughes & Wright, 1970).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies on the structure of fish gills have focused on the dependence of the total surface area of the gill upon the body size and species of fish (1,4,5). We consider the convective oxygen transfer that occurs in fish gills.…”
mentioning
confidence: 99%